2018
DOI: 10.1590/2446-4740.03717
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed doses in salivary and thyroid glands from panoramic radiography and cone beam computed tomography

Abstract: Panoramic radiography and cone beam computed tomography (CBCT) are very important in the diagnosis of oral diseases, however patients are exposed to the risk of ionizing radiation. This paper describes our study aimed at comparing absorbed doses in the salivary glands and thyroid due to panoramic radiography and CBCT and estimating radiation induced cancer risk associated with those methods. Methods: Absorbed doses of two CBCT equipment (i-CAT  Next Generation and SCANORA  3D) and a digital panoramic device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As shown in table 5, the highest organ absorbed dose was found in the salivary glands and then oral mocusa in both CBCT and panoramic examinations. In general, the absorbed dose value is higher significantly in CBCT in comparison with panoramic because of the higher X-ray setting factors and the different geometry of CBCT (1,10,23,26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in table 5, the highest organ absorbed dose was found in the salivary glands and then oral mocusa in both CBCT and panoramic examinations. In general, the absorbed dose value is higher significantly in CBCT in comparison with panoramic because of the higher X-ray setting factors and the different geometry of CBCT (1,10,23,26) .…”
Section: Discussionmentioning
confidence: 99%
“…Following our investigation, the previous studies have reported the REID values for children or/and adults in panoramic radiography (10,15,16) , or only for CBCT (15,17) . In the present study, we obtained the dose-area product (DAP), organ doses, effective dose, cancer risk and REID values for two different patient groups in CBCT and panoramic radiographies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported doses with different CBCT scanner equipment, technical protocol settings, and their role in radiation output. Ghanbarnezhad Farshi et al [14], reported SED to different organs of the head and neck with a phantom using three CBCT units, NewTom VGi (NewTom) and Planmeca Promax 3D (Planmeca, Helsinki, Finland), in another study Heiden et al [15], in Brazil reported a study performed on a phantom with i-CAT Next Generation (Imaging Sciences International) and SCANORA 3D, using thermoluminescent dosimeter placed on the thyroid surface. The mean absorbed dose to thyroid surface in i-CAT device ranged between 0.02 and 2.23 mGy, from SCANORA 3D dose ranged from 0.01 to 2.96 mGy.…”
Section: Jrprmentioning
confidence: 99%
“…However, the main drawback of cross sectional imaging is the higher radiation dose compared to radiography, even though several studies showed a lower radiation dose for CBCT than for conventional multidetector computed tomography (MDCT) [1,2].This implies that many radiation sensitive organs such as the salivary glands are exposed to the x-ray beam without being depicted and thus with no diagnostic value. Therefore, several studies examined the distribution of organ and effective doses in CBCT, showing that the salivary glands, the remainder tissue and the thyroid are the most exposed organs [4][5][6]. With numerous manufacturers and devices on the market, CBCT scanners differ significantly in their buildup and their settings such as fields of view (FOV), setting of the isocenter, positioning of the rotational arc and dose protocols, leading to differences in amount and distribution of dose and making it difficult to draw comparisons between the devices and, furthermore, to define standard exposition values that apply for all devices [7].…”
Section: Introductionmentioning
confidence: 99%